Pengaruh Kualitas Produk, Harga Dan Kenyamanan Tempat Terhadap Kepuasan Konsumen Pada Warung Joker - Salwa, Ahmad Afiq; Wahono, Budi; Basalamah, Muhammad Ridwan (UNIVERSITAS ISLAM MALANG, 2024)
AbstractÂ The aim of this research is to determine and analyze the influence of product quality, price and comfort of place on consumer satisfaction at Joker Stalls. Quantitative research is the focus of this research. The data used in this research is primary data. The data collection method used was a questionnaire. The data anaysis method used in this research uses multiple linier regression analysis. The population in this research is warung Joker consumers. The sample in this study was 80 respondens. The result of this research are that product quality, price and comfort of the place have a significant effect on consumer satisfaction at Joker Stalls simultaneously and partially.Â Keywords: Product Quality, Price, Confort of Place, Consumer Satisfaction.